Forecast Accuracy Comparison Between Holt’s Method and the Box-Jenkins Approach: The Case of Madiun City Labor Force Participation Rate - Muhammad Qolbi Shobri; Yan Aditya Pradana; Putri Balqis Al-Kubro; Nayla Desviona; Nila Destia Nasra (Departemen Statistika Universitas Negeri Padang, 2025)
Pacitan district recorded the highest Labor Force Participation Rate (LFPR) in Eastern Java Province. Meanwhile, Madiun city which is one of the largest cities in East Java Province, is ranked only 34 out of 39 cities in 2023. This condition raises concern for the local government, perticularly the Department of Manpower,in ensuring that the productive-age population can be optimally absorbed into the labor market. The LFPR is categorized as time series data, thus forecasting method are required to estimate its future trends.This Study compares the performance of the Double Exponential Smoothing Holt (DESH) method and the Autoregressive Integrated Moving Average (ARIMA) Box-Jenkins approach in forecasting the LFPR of Madiun City. The empirical result show that the ARIMA (1,0,1) model provides better accuracy compared to DESH. The forecasting result indiacte that the LFPR of Madiun City is project to reach 67,19% in 2024, 67,20% in 2025, and 67,21% in 2026, with Mean Squared Error (MSE) of 14,48; Root Mean Square Error (RMSE) of 3,80 and Mean Absolute Percentage Error (MAPE) of 4,75%. These finding are expected to serve as reference for future research and practical input for policymakers in formulating strategies to improve labor LFPR in Madiun City.